UJI PERBANDINGAN EFEKTIFITAS DAUN SENDUDUK (MELASTOMA MALABATHRICUM L.) DENGAN BETADIN TERHADAP WAKTU PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH JANTAN GALUR WISTAR - ASMAUL HABIBI; ILHAM HARIAJI (LP2MTBM MAKARIOZ, 2022)
The wound is a break in the continuity (continuity) of the tissue followed by a part of the tissue structure. If not treated properly, cuts can be life-threatening. This research purpose To know the comperation of effectiveness senduduk leaf healing time on male white wistar rats. this research is an experimental posttest-only control-group design with a total sampling of 20 rats, and divided into four groups;negative control, betadine, 10 gr of senduduk leaves and 15 gr of senduduk leaves. Data will be analyzed by Kruskal Wallis and Mann-Whitney test. The resulth of this research are Average healing time (tp=11,80 betadin=10,60 p1=9,90 p2=8,50). Data analysis obtained significant results (p <0.05), namely between the negative control group with betadin, negative control group with 10 gr of senduduk leaves, negative control group with 15 gr of senduduk leaves, betadin group with 15 gr of senduduk leaves. Meanwhile the other groups obtained insignificant results (p>0.05).